O potencial do Turismo de Base Comunitária (TBC) em território camponês: um estudo no Assentamento 72 em Ladário, MS - Zanetoni, Joao Pedro Ferraz (2022)
Peasant territory is the result of relations between social actors in the countryside. In it, it is possible to find two ways of doing agriculture, manifesting different territorialities. The capitalist mode of production in the countryside is marked by technological advancement, massive productivity, competitiveness and monopolization of space. The peasant mode of production is marked by factors of associativism, self-sufficiency and family autonomy, characteristics that have been lost and with that, leading peasants to lose space for production and social reproduction. They are distinct forms of territorialization of space that led to socio-territorial conflicts, and resulted, among other things, in the creation of rural settlements. Settlements are the manifestation of the peasant struggle that territorialize their space through cooperation and the search for autonomy, adhering to joint production practices without the use of pesticides, creation of residents' associations, direct marketing with consumers, among other practices that mark their search. for emancipation. However, it is not uncommon to find peasants in rural settlements who see themselves in a position of subordination to the market, manifesting territorialities that contradict the peasant logic but seeking autonomy. In this sense, Community-Based Tourism (CBT) is an endogenous and emancipatory activity, which values ​​local territorialities and proposes autonomy, appreciation and collective participation for the community. The general objective of the work is to understand the peasant territorialities that allow fields for the implementation of community-based tourism (CBT) initiatives in Assentamento 72, in Ladário - MS. As for the methodological procedures, the present research is of an exploratory and descriptive nature, with a qualitative approach, the Territorial Approach and techniques of Thematic Oral History were used for data collection, and the interpretations were made using Content Analysis, with the help of the Software IRAMUTEQ. The results allowed a multidimensional understanding (political, economic, environmental and sociocultural) of peasant territorialities in the settlement, identifying relationships of associativism, collective management around agroecological production, culminating in the elaboration of an informal association of local producers. Potential to develop tourist activity was noted from this group, in view of the way in which they are collectively organized, the natural landscapes and the agroecological gardens, which allow for tours, in addition to the partnerships identified with teaching and research institutions. However, it should be noted that the group does not represent the entire settlement, and there is isolation between them and the rest of the peasants, the association of local residents could act as a link between the entire settlement, but it does not, in addition, the settlement struggles daily to obtain potable water, a historical problem that has not been resolved. Some notes were made in order to implement CBT initiatives, considering this reality. There is potential to develop tourist activity in the settlement, but it is not yet possible to talk about the settlement as an aligned community.